2013
DOI: 10.1097/md.0000000000000008
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium Infection

Abstract: Fusarium species is a ubiquitous fungus that causes opportunistic infections. We present 26 cases of invasive fusariosis categorized according to the European Organization for Research and Treatment of Cancer/Mycoses Study Group (EORTC/MSG) criteria of fungal infections. All cases (20 proven and 6 probable) were treated from January 2000 until January 2010. We also review 97 cases reported since 2000. The most important risk factors for invasive fusariosis in our patients were compromised immune system, specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(55 citation statements)
references
References 132 publications
2
53
0
Order By: Relevance
“…Although case series of Fusarium infections have been reported throughout the years (4,7,9,16,(20)(21)(22), only in a recent report was an indication of a potential correlation between MICs for Fusarium spp. and response to treatment found (22), where CLSI MICs for seven Fusarium isolates identified by molecular methods, antifungal therapy (voriconazole or both voriconazole and amphotericin B), and clinical response were documented for patients with invasive fusariosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although case series of Fusarium infections have been reported throughout the years (4,7,9,16,(20)(21)(22), only in a recent report was an indication of a potential correlation between MICs for Fusarium spp. and response to treatment found (22), where CLSI MICs for seven Fusarium isolates identified by molecular methods, antifungal therapy (voriconazole or both voriconazole and amphotericin B), and clinical response were documented for patients with invasive fusariosis.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent causes of fungal infections are members of three complexes, the F. solani species complex (SC), the F. oxysporum SC, and the Fusarium (Gibberella) fujikuroi SC (which includes, among others, F. verticillioides and F. proliferatum), and the next most frequent causes belong to the F. dimerum SC and F. incarnatum-F. equiseti SC; their distribution could be region dependent (4,(7)(8)(9)(10). Common clinical presentations are onychomycosis, keratitis, allergic disease (sinusitis and bronchopulmonary disease) for nonimmunocompromised patients and disseminated disease, as well as other severe invasive infections, in immunocompromised hosts (e.g., patients with prolonged neutropenia and T-cell immunodeficiency) (1,4,(7)(8)(9)(10)(11)(12)(13). Amphotericin B lipid formulations, voriconazole, posaconazole, and, to a lesser extent, itraconazole have been recommended or used for the treatment and prophylaxis of Fusarium infections, in addition to surgical debridement and reversal of immunosuppression (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10, 11, 12, 13, 14, 15, 16 Nucci et al 17 reported 233 cases from different hospitals on a global scale. Mohammed et al 18 reported 26 cases from the United States and reviewed 97 cases from the literature, and Horn et al 12 described 65 cases from the North American Path Alliance Registry. A major problem in comparative studies is the subdivision of the classical species into a series of molecular siblings, which renders the older literature without sequence data uninterpretable.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years other fungi emerged as important infections agents, including yeast species such as non-albicans Candida species, Cryptococcus sp., Trichosporon spp., and Rhodotorula spp. and filamentous fungi such as Fusarium spp., Rhizopus spp., Rhizomucor spp., and phaeohyphomycosis agents (Sun et al, 2012;Juyal et al, 2013;Kim et al, 2013;Muhammed et al, 2013;Jaın et al, 2014;Schieffelin et al, 2014).…”
Section: Fungus: Overall Look In the Main Topicmentioning
confidence: 99%